MOF-derived Cobalt Sulfide Grown on 3D Graphene Foam as an Efficient Sulfur Host for Long-Life Lithium-Sulfur Batteries - He, Jiarui; Chen, Yuanfu; Manthiram, Arumugam (iScience, 2018)
Lithium-sulfur (Li-S) batteries are an appealing candidate for advanced energy storage systems because of their high theoretical energy density and low cost. However, rapid capacity decay and short cycle life, mainly resulting from polysulfide dissolution, remains a great challenge for practical applications. Herein, we present a metal-organic framework (MOF)-derived Co9S8 array anchored onto a chemical vapor deposition (CVD)-grown three-dimensional graphene foam (Co9S8-3DGF) as an efficient sulfur host for long-life Li-S batteries with good performance. Without polymeric binders, conductive additives, or metallic current collectors, the free-standing Co9S8-3DGF/S cathode achieves a high areal capacity of 10.9 mA hr cm−2 even at a very high sulfur loading (10.4 mg cm−2) and sulfur content (86.9 wt%). These results are attributed to the unique hierarchical nanoarchitecture of Co9S8-3DGF/S. This work is expected to open up a promising direction for the practical viability of high-energy Li-S batteries. [Display omitted] •Metal-organic framework-derived Co9S8 arrays are grown onto 3D graphene foam•Co9S8-3DGF serves as a free-standing, binder-free host for sulfur cathodes•Co9S8-3DGF/S cathode exhibits high capacity with long cycle life•Co9S8-3DGF/S cathode displays a remarkably high areal capacity Inorganic Chemistry; Energy Materials; Porous Material